2014
DOI: 10.5301/jva.5000211
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Balloon for the Treatment of Failing Hemodialytic Radiocephalic Arteriovenous Fistulas: Our Experience in the Treatment of Juxta-Anastomotic Stenoses

Abstract: The use of drug-eluting balloons, after standard angioplasty, improves primary patency and decreases reinterventions of TL in juxta-anastomotic stenoses of failing native dialytic arteriovenous shunts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 53 publications
3
49
1
Order By: Relevance
“…Primary lesion patency was significantly better after PCB at 6 months but not at 1 year (70% vs 0% [P < .01] at 6 mo; 20% vs 0% [P > .05] at 1 y) (16). Patane et al (17) treated juxtaanastomotic stenosis of AVFs in a single-center, single-arm prospective study and reported a 1-year primary patency rate of 91% in 26 patients. To our knowledge, the only study that actually explored the use of PCB in CVS was a retrospective analysis by Massmann et al (26) in which central and peripheral veins in dialysis access circuits were treated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Primary lesion patency was significantly better after PCB at 6 months but not at 1 year (70% vs 0% [P < .01] at 6 mo; 20% vs 0% [P > .05] at 1 y) (16). Patane et al (17) treated juxtaanastomotic stenosis of AVFs in a single-center, single-arm prospective study and reported a 1-year primary patency rate of 91% in 26 patients. To our knowledge, the only study that actually explored the use of PCB in CVS was a retrospective analysis by Massmann et al (26) in which central and peripheral veins in dialysis access circuits were treated.…”
Section: Discussionmentioning
confidence: 95%
“…Paclitaxel-coated balloons (PCBs) have been tested for their safety and efficacy in the treatment of dysfunctional dialysis access in a few randomized studies and retrospective analysis of cases, with encouraging results so far (14)(15)(16)(17)(18). In two randomized controlled trials that used PCBs in arteriovenous fistulae (AVFs) and the venous outflow of arteriovenous grafts (AVGs) (14,15), the use of PCBs demonstrated significantly better results than conventional angioplasty.…”
mentioning
confidence: 96%
“…Elastic or rigid stenoses can be treated by conventional PTA and stent implantation as well as by cutting balloon, for example [10,11]. To prevent recurrent stenoses, the use of drug-coated balloons is increasingly being reported [12,13]. There are currently no randomized studies or even larger case series showing a superior long-term patency rate for endovascular brachytherapy [14,15] and cryoplasty [16].…”
mentioning
confidence: 99%
“…At 6 months, primary target lesion patency following angioplasty with PCB was reported in previous studies to range from 44 to 97%. These findings were higher than the 6‐month circuit patency of 42.9% of all accesses reported in our study.…”
Section: Discussionmentioning
confidence: 63%